Systems Analysis of Immunity to Influenza Vaccination across Multiple Years and in Diverse Populations Reveals Shared Molecular Signatures - Nakaya, Helder I.; Hagan, Thomas; Duraisingham, Sai S.; Lee, Eva K.; Kwissa, Marcin; Rouphael, Nadine; Frasca, Daniela; Gersten, Merril; Mehta, Aneesh K.; Gaujoux, Renaud; Li, Gui-Mei; Gupta, Shakti; et al. (Immunity (Cambridge, Mass.), 2015)
Systems approaches have been used to describe molecular signatures driving immunity to influenza vaccination in humans. Whether such signatures are similar across multiple seasons and in diverse populations is unknown. We applied systems approaches to study immune responses in young, elderly, and diabetic subjects vaccinated with the seasonal influenza vaccine across five consecutive seasons. Signatures of innate immunity and plasmablasts correlated with and predicted influenza antibody titers at 1 month after vaccination with >80% accuracy across multiple seasons but were not associated with the longevity of the response. Baseline signatures of lymphocyte and monocyte inflammation were positively and negatively correlated, respectively, with antibody responses at 1 month. Finally, integrative analysis of microRNAs and transcriptomic profiling revealed potential regulators of vaccine immunity. These results identify shared vaccine-induced signatures across multiple seasons and in diverse populations and might help guide the development of next-generation vaccines that provide persistent immunity against influenza. •Systems analysis of vaccine immunity to influenza across seasons and populations•Signatures of innate immunity and plasmablasts predicted influenza antibody titers•Certain vaccine-induced signatures were shared among all analyzed populations•Defined baseline signatures of immunogenicity that might help guide vaccine design Pulendran and colleagues describe a systems-based approach to study immunity to influenza vaccination in healthy adults, the elderly, and diabetics across five influenza seasons. They found that molecular signatures induced in the blood days after vaccination predicted the immunogenicity of the vaccine in adults and the elderly across multiple seasons.